Penerapan model pembelajaran kooperatif tipe take and give untuk meningkatkan keterampilan berkomunikasi dalam pembelajaran IPS pada peserta didik kelas V sekolah dasar - Juvita Oktaviyani; Hadi Mulyono; Hadiyah Hadiyah (Didaktika Dwija Indria, 2020)
The purpose of this research is improve communication skills in social studies learning with applying the cooperative learning model type take and give for fifth grade students of SD Negeri Tegalrejo No.98. This research is Classroom Action Research is conducted in two cycles. The subject of this research were teachers and fifth grade students of SD Negeri Tegalrejo No.98 2019/2020 academic year, totality of 30 students. This research used the technique of collecting data in the form of interviews, observation, and documentation. Test the validity of the data using content validity and triangulation. The data analysis technique used is an intercative analysis model Miles-Huberman. The results communication skills in pre-action of the fifth grade students showed percentage 36,67% clasically. The first cycle with the first learning percentage of 48,27% and the second learning percentage of 57,14% clasically. The second cycle has increased is the first learning percentage 71,42% and the second learning percentage of 83,33%. Based on the results of the research, it was concluded that: the application of cooperative learning model type take and give can improve communication skills in social studies. Keywords: communication skills, cooperative learning model type take and give, social studies learning, elementary school